The South African press as watchdog or lapdog : a content analysis of press coverage of a health policy May 1997-February 1998 - Powell, Anel Elaine (Stellenbosch : Stellenbosch University, 2012)
Study report (M. Phil.) -- University of Stellenbosch, 1998.